Randomized, Comparative Study of Full- and Half-Dose Fluorescein Angiography. (July 2021) - Patel, Vaama; Syeda, Sarah; Zeiter, John; Nassiri, Nariman; Kim, Chaesik; Truhan, Alan; Chapman, Christopher; Adam, Christopher; Parendo, Anthony; Savage, Mack; Abrams, Gary
Purpose: This study determines whether fluorescein angiography (FA) with a 250-mg dose of fluorescein (half dose) is equal in quality to the standard 500-mg dose of fluorescein (full dose) when using digital ultra-widefield (UWF) technology. Methods: In a randomized, prospective study using a UWF imaging system, FAs performed with half dose were compared with angiograms performed with full dose. Imaging studies were reviewed by 4 reviewers based on 6 characteristics: dye transit, macrovasculature, macula detail, microvasculature, leakage, and overall quality. The scores for macrovasculature, macula detail, microvasculature, and overall quality were converted to a fuzzy rating score to confirm results. Results: Seventy-nine FAs from 67 patients were reviewed for this study, including 12 patients who had both half-dose and full-dose FAs. Of all the factors studied, only microvasculature received a significantly different score between full dose and half dose that was confirmed by the fuzzy rating scale (3.79 vs 3.53; P  = .04). Among those eyes that received both full and half dose, there was no significant difference in any of the 6 factors. Conclusions: In a UWF imaging system, aside from looking at fine microvascular abnormalities, the 250-mg dose of fluorescein provided similar results to a 500-mg dose. The images were not significantly different in overall quality.